Monsieur Eek - Ives, David (New York HarperCollins, 2001)
When a chimpanzee arrives in MacOongafoondsen he is put on trial for being a thief and a French spy, resulting in some changes to the tiny town that delight Emmaline Perth, his thirteen-year-old defender.
800L
78798
Keywords: Chimpanzees -- Fiction; Trials -- Fiction; Humorous stories